Using the Heat Moisture Treatment Technique (HMT) to Improve Lima Bean Quality - Fatima, Sariya (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Hipocotyl Bruguiera gymnorrhiza High carbohydrate, but in Indonesia has not been exploited and developed, this is an alternative hypocotyl development for manufacturing starch as food ingredients industry. In addition to looking for new sources of starch for the modern food industry, also need to know the functional properties of starch. s. The purpose of this study was to determine the effect of sodium bisulfite solution concentration and temperature of heating and the interaction against best quality starch. In this study, the concentration of sodium bisulfite and heating temperature as a variable is changed, while the fixed variables are time and temperature of drying. The study was conducted using a completely randomized factorial design with three replications with 2 factors that NaHSO3 concentration of 0.10%, 0.20%, 0.25% and 0.40% and heating temperature 40 °C, 50 °C and 6 °C. Verse data processing using SPSS 16.0. These results indicate that treatment factors temperature and concentration on the extraction of starch hipocotyl Bruguiera gymnorrhiza significant effect (P < 0.01) of the amylose content, starch content, viscosity, solubility and reduced sugar. Interaction heating temperature and concentration also had a significant effect on amylose content, starch content, viscosity, solubility and reduced sugar. Treatment with a heating temperature of 60 °C and the concentration of 0.25% for 5 minutes is the best treatment result was 19,58 % amylose content, starch content of 65.00%, 520.33 cP viscosity, solubility and reducing sugar 91.99% 0.27%.